Antimicrobial effect of cocoa peels aqueous extracts and cocoa seeds (Theobroma Cacao) In a streptococcus mutans strain: In vitro study - Sucuzhañay Mora, Miryan Alexandra (2018)
Objective: Evaluate the antimicrobial effect of cocoa peels aqueous extracts and cocoa seeds (Theobroma Cacao) in a Streptococcus Mutans strain. Methods and Equipment: In this experimental study, the sample consisted on 20 petri dishes inoculated with Streptococcus mutans ATTCC 25175 that were reactivated in Agar blood for 24 hours and cultured at 35°C +/- 2ºC. A reflux method, using distilled water as a solvent, was used in order to obtain the aqueous extracts. These extracts were fixed in a 12.5% and 20% concentration ratio. The Mann Whitney U test obtained a significance level of 5%. Results: There were no meaningful differences between the peels aqueous extracts and the seed inhibition halo at a 12.5% concen-tration (p=0,27) and at a 20% concentration (p= 0.94); these two extracts have the same antimicrobial effect. Conclusions: The cocoa peels aqueous extracts and cocoa seeds showed antimicrobial effect over Streptococcus Mutans.